1, 3, 5-Pentanetricarbonitrile additive for improving high voltage stability of lithium cobalt oxide cells. (1st October 2018) - Duan, Boyu; Hong, Bo; Li, Jie; Qin, Zhaoming; Jiang, Feng; Lai, Yanqing
Abstract: In this work, 1, 3, 5-Pentanetricarbonitrile (PTN) is adopted as a novel electrolyte additive to improve the electrochemical characteristics of LiCoO2 cathode operating under high charging cut-off voltage. PTN additive generates an extremely stable CEI film with abundant of CN bond and higher content of Lix POy Fz /Lix PFy on the LiCoO2 cathode surface, which is beneficial to inhibit the continuous decomposition of electrolyte and decrease the interfacial impedance. With electrolyte containing 0.5 wt.% PTN, the LiCoO2 cathode shows an initial capacity of 180.1 mAh g −1 with a columbic efficiency of 94.0%, and achieves a capacity retention of 90.7% for 300 cycles at 3.0–4.45 V. It makes the mass specific energy density of LCO cathode increases from 564.7 Wh kg −1 to 728.7 Wh kg −1, which leads to nearly 30% of the additional energy.